A bout de souffle [videorecording (DVD)] - Godard, Jean-Luc, 1930-; Truffaut, François; Belmondo, Jean-Paul, 1933-2021-; David, Liliane; Seberg, Jean (Fox Lorber Films : Distributed by WinStar TV & Video, 2001)
A small-time hood kills a policeman and tries to leave France, but his American girlfriend betrays him to the police and he gets killed trying to escape.